Fertilization influences the substrate, rhizosphere, and endosphere bacteriome of Petunia × hybrida - Quijia-Pillajo, Juan; Chapin, Laura J.; Owen, James S.; Altland, James E.; Jones, Michelle L. (Frontiers in Microbiology, 2025)
IntroductionIn controlled environment agriculture (CEA), soil is replaced with soilless substrates that have poorly understood microbiome dynamics. We investigated the rhizosphere and endosphere bacteriome of Petunia × hybrida ‘Picobella Blue’ (Picobella) and ‘Wave Purple’ (Wave) grown in a soilless substrate (80% sphagnum peat and 20% perlite) under three fertilization rates (25, 100, and 200 mg·L−1 N).MethodsPlant growth was assessed with the TraitFinder phenotyping platform, shoot dry weight, and nutrient analysis. Bacteriomes were profiled by 16S rRNA amplicon sequencing from unplanted substrate, bulk substrate, rhizosphere, and endosphere samples.ResultsBoth cultivars grew largest and healthiest at 200 mg·L−1 N. Picobella fertilized with 100 and 200 mg·L−1 N were equally green, whereas Wave was greenest at 200 mg·L−1 N. Distinct bacteriomes were observed across unplanted substrate, rhizosphere, and endosphere. In unplanted substrate, fertilizer rate shaped bacterial community composition but not alpha diversity. In the rhizosphere, pH changes driven by fertilization strongly influenced bacterial community structure and reduced diversity. Endosphere and rhizosphere communities were further shaped by cultivar and fertilization rate.DiscussionThese findings highlight nutrient management as a key driver of bacteriome dynamics across the substrate–plant continuum, underscoring the complex interactions between fertilization, plant genotype, and microbial communities in soilless culture.